1995
DOI: 10.1159/000316230
|View full text |Cite
|
Sign up to set email alerts
|

Does Amalgam Affect the Immune System? A Controversial Issue (Part 2 of 2)

Abstract: Although in use for more than 150 years, dental amalgam has been questioned more or less vigorously as a dental restoration material due to its alleged health hazard. Humans are exposed to mercury and the other main dental amalgam metals (Ag, Sn, Cu, Zn) via vapour, corrosion products in swallowed saliva, and direct absorption into the blood from the oral cavity. Dental amalgam fillings are the most important source of mercury exposure in the general population. Local, and in some instances, systemic hypersens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Second, exposure of humans to mercury is associated with lupus-like autoimmune disease (37), and mice treated with inci-cury develop autoantibodies directed against the nucleolar protein fibrillarin in a genetically-restricted manner (38). Treatment of cells in vitro with mercury rcsults in cell death and inhibition of cysteinc crosslinking of fibrillarin, a niodification that has been proposed to change the antigenicity of the molecule (39).…”
Section: Modifications Of Autoantigens During Cell Deathmentioning
confidence: 99%
“…Second, exposure of humans to mercury is associated with lupus-like autoimmune disease (37), and mice treated with inci-cury develop autoantibodies directed against the nucleolar protein fibrillarin in a genetically-restricted manner (38). Treatment of cells in vitro with mercury rcsults in cell death and inhibition of cysteinc crosslinking of fibrillarin, a niodification that has been proposed to change the antigenicity of the molecule (39).…”
Section: Modifications Of Autoantigens During Cell Deathmentioning
confidence: 99%
“…It has been shown that mercury causes type I and IV allergic reactions, and in vitro sensitizes rat peritoneal mast cells for the Fc⑀RI-mediated mediator release (1)(2)(3)(4). Mercury is well known to induce autoimmunity in genetically susceptible humans (5) or experimental animals.…”
mentioning
confidence: 99%
“…There are many reports on modifications of nuclear antigens that may lead to increased immunogenicity of nuclear antigens, e.g. phosphorylation or dephosphorylation [25,27], citrullization [28], oxidative stress in combination with heavy metals [29], mercury intoxication [30][31][32], the activation of transglutaminases [33], or acetylation [25]. In addition, Rosen et al [11] were able to show that in Sindbis-virus-induced apoptosis of keratinocytes viral and nuclear cellular antigens were colocalized in the apoptotic surface blebs.…”
Section: Increased Amounts and Abnormal Presentation Of Nuclear Antigensmentioning
confidence: 99%